Palliative radiotherapy in symptomatic locally advanced gastric cancer: A phase II trial. (20th February 2019) - Tey, Jeremy; Zheng, Huili; Soon, Yu Y.; Leong, Cheng N.; Koh, Wee Y.; Lim, Keith; So, Jimmy B. Y.; Shabbir, Asim; Tham, Ivan W. K.; Lu, Jiade
Abstract: To evaluate the response and quality of life of palliative gastric radiotherapy in patients with symptomatic locally advanced gastric cancer. Patients with bleeding, pain or obstruction and were treated with palliative gastric radiotherapy to a dose of 36 Gy in 12 daily fractions. The primary outcomes were symptom response rates. Secondary outcomes included overall survival, adverse events and proportion of patients with ≥10‐point absolute improvement in the fatigue, nausea/vomiting and pain subscales in the EORTC Qualify of Life Questionnaire C30 (EORTC QLQ‐C30) and dysphagia/pain subscales in the gastric specific module (STO22) at the end of RT and 1 month after the completion of radiotherapy. Fifty patients were accrued. Median survival duration was 85 days. 40/50 patients (80%) with bleeding, 2/2 (100%) patients with obstruction and 1/1 (100%) patient with pain responded to radiotherapy. Improvements fatigue, nausea/vomiting and pain subscales of the EORTC QLQ‐C30 was seen in 50%, 28% and 44% of patients at the end of RT and in 63%, 31% and 50% of patients 1 month after RT. Improvements in dysphagia/pain subscales of the STO22 was seen in 42% and 28% of patients at then end of RT and 44% and 19% of patients 1 month after RT. Two patients (5%) had grade 3 anorexia and gastritis. Palliative gastric radiotherapy was effective, well tolerated and resulted in improvement in fatigue, dysphagia and pain at the end of radiotherapy and 1 month after the completion of radiotherapy in a significant proportion of patients. Abstract : 50%, 28% and 44% of patients had improvements in fatigue, nausea/vomiting and pain subscales of the EORTC QLQ‐C30, 42% and 28% of patients achieved improvements in dysphagia and pain subscales of the STO22 at the end of palliative gastric radiotherapy.